Educadores/as em forma????o diante da viol??ncia sexual infanto-juvenil: um estudo explorat??rio do Programa Escola que Protege ?? luz da psicodin??mica do trabalho - Miranda, Adriana Costa de (2017)
This research presents an analysis about the training of educators/participants in the extension course taught in-person and online as part of the National Program Escola que Protege offered by the Centro de Estudos Psicol??gicos sobre Meninos(as) de Rua da Universidade Federal do Rio Grande do Sul ??? CEP-Rua/UFRGS. This course addresses violence against children and in the school environment; and how to prevent and break the cycle of this kind of violence. The objective was to analyze the organizational, theoretical and methodological strategies of the course as well as the subjective impact of sexual violence against children and teens on the educators. The abuse and sexual exploitation against children and teens are serious social phenomena that affect millions of people all over the world that can provoke physical, psychological, emotional harm in social relations and learning. The focus of the research is on the creators of the National Program Escola que Protege course and the educators given that they are in a position to confront sexual violence against children and teen through notifying child and teen protection entities and engaging in preventive actions in schools. This research is an exploratory and qualitative study that was carried out based on the psychodynamic of work theory, which deals with the relation between work and mental health. Given the detailed and diverse collection of information in the case study, the research was conducted through documentary analysis; non-participant observation and open interviews. Through the interviews, 15 educators and 4 trainers from the Escola que Protege were observed. The analysis of the research results were divided in two phases: (I) Structure of the course Escola que Protege and, (II) Work and training to confront sexual violence against children and teens. Triangulation analysis showed that contact with the sexual violence thematic involves subjectivity and makes it difficult for the educators; this demonstrated that the search for the course is in itself a way for the educators to deal with the actual work; and showed that the organization and work conditions in schools can incentivize educators to avoid the issue. It is also worth noting that the educator is not neutral regarding this violence that affects the body of the child and the adolescent; on the contrary, this experience can summon her/his history in relation to her/his sexuality, its erotic body and her/his relation with the adults. This research emphasizes the importance to create collective spaces for listening and speaking, in order to recognize the subjective impact of sexual violence against children and teens on the educators; and to encourage the exchange of experiences that enable notification of sexual violence cases to the appropriate parties; and, projects that allow preventive interventions in schools. It is understood that in this kind of training, it is necessary to take into account the work in the context of sexual violence against children and teens, which requires attention to the prescribed and the actual work. It is also emphasized that the National Program Escola que Protege offered by CEP-Rua integrates the learning, research and extension tripod, contributing to the advancement of public policy.